Pengaruh Secondary Aging Treatment Terhadap Sifat Mekanik Dan Surface Glossiness Pada Aluminium Paduan 7003 - Ramli Ramli (Manutech : Jurnal Teknologi Manufaktur, 2017)
As technology advances and the quality of life improves, there is a deep need that requires of aluminium alloy that bears high strength, high toughness, high surface glossiness, anti-corrosion, and high fatigue resistivity [2]. This study aims to investigate the effects of secondary aging treatment on the mechanical properties and Surface Glossiness of the 7003 aluminium alloy by using several equipment, including: confocal laser microscope, white light interferometer, gloss meter, micro Vickers hardness tester and tensile test machine. This research was conducted by experimental method by giving treatment on the aluminium alloy 7003 with some treatments, there are: aging treatment at 100?C for 5 hours and then secondary aging treatment at several different temperatures at 150?C, 175?C and 200?C for 9 hours respectively. Based on our experimental results, it obtained: After being aged at 100 ? for 5 hours and then secondary aged at 175? for 9 hours, the 7003 aluminium alloy obtained excellent mechanical properties, which can achieve the industrial requirements of Yield strength 320 MPa and Elongation 13% for 3C mobile phone products. The 7003 aluminium alloy after being anodizing treated could obtain excellent Surface Glossiness and oxidation layer. The present aluminium alloy can achieve Surface Glossiness better than 1200 GU and the thickness of oxidation layer exceed 10?m, which were suitable for 3C industrial applications.